2005
DOI: 10.1080/00365540510012170
|View full text |Cite
|
Sign up to set email alerts
|

Human leptospirosis in eastern Croatia, 1969–2003: Epidemiological, clinical, and serological features

Abstract: This survey presents epidemiological, serological and clinical features of 270 patients (85% males, 18% children) treated for leptospirosis from 1969 to 2003 at the Clinic for Infective Diseases, University Hospital Osijek, Osijek, eastern Croatia. 75% of the admissions were between July and October. The route of transmission was mostly by indirect contact with domestic animals, less frequently by direct contact with urine or tissue of infected animals. Clinical presentation included signs and symptoms with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
3
1
0
1
Order By: Relevance
“…Serogrouping of isolates revealed that 10/20 belong to serogroup Pomona, 6/20 to serogroup Australis, 2/20 to serogroup Sejroe, 1/20 to serogroup Bataviae and 1/20 to serogroup Grippotyphosa. These results correlate to the latest serological surveys on human leptospirosis in Eastern Croatia which reports Pomona, Australis and Sejroe as the most prevalent serogroups (Peric et al, 2005; Cvitkovic, 2007). In this study 9/10 (90.0%) of L. kirschnerii serovar Mozdok serogroup Pomona were isolated from A. agrarius , which confirms this species as natural host of L. interrogans serogroup Pomona (Borcic et al, 1986).…”
Section: Discussionsupporting
confidence: 87%
“…Serogrouping of isolates revealed that 10/20 belong to serogroup Pomona, 6/20 to serogroup Australis, 2/20 to serogroup Sejroe, 1/20 to serogroup Bataviae and 1/20 to serogroup Grippotyphosa. These results correlate to the latest serological surveys on human leptospirosis in Eastern Croatia which reports Pomona, Australis and Sejroe as the most prevalent serogroups (Peric et al, 2005; Cvitkovic, 2007). In this study 9/10 (90.0%) of L. kirschnerii serovar Mozdok serogroup Pomona were isolated from A. agrarius , which confirms this species as natural host of L. interrogans serogroup Pomona (Borcic et al, 1986).…”
Section: Discussionsupporting
confidence: 87%
“…Other increased laboratory markers correlated more strongly with severity of clinical presentation of leptospirosis (). Comparative results were found also in other studies [7, 8, 24, 30].…”
Section: Discussionsupporting
confidence: 87%
“…Seroepidemiological and seroepizootiological studies in Croatia based on the MAT test have shown changes in the incidence of probable infectious serogroup in both animals and humans. Studies show continuous presence of Grippotyphosa and Icterohaemorrhagiae serogroups, reduced frequency of Sejroe (serovar Saxkoebing), and increasing frequency of Australis serogroup [14,16,22,30,31]. In the period of our study, serogroup Icterohaemorrhagiae remained dominant (Table 1).…”
Section: Discussionsupporting
confidence: 56%
“…Es igualmente común la elevación de los niveles de las enzimas musculares, como la creatín-fosfocinasa. En los pacientes con meningitis existe pleocitosis, que inicialmente es polimorfonuclear, pero posteriormente se transforma en mononuclear; la proteinorraquia también suele aumentar, pero la glucorraquia suele ser normal 10 .…”
Section: Alteraciones Analíticasunclassified